Mycotoxin Research - Mycotoxin Research (Springer Nature, 2026)
Mycotoxin Research, the official publication of the Society for Mycotoxin Research, is a peer-reviewed, scientific journal dealing with all aspects related to toxic fungal metabolites. The journal publishes original research articles and reviews in all areas dealing with mycotoxins. As an interdisciplinary platform, Mycotoxin Research welcomes submission of scientific contributions in the following research fields: Ecology and genetics of mycotoxin formation; Mode of action of mycotoxins, metabolism and toxicology; Agricultural production and mycotoxins; Human and animal health aspects, including exposure studies and risk assessment; Food and feed safety, including occurrence, prevention, regulatory aspects, and control of mycotoxins; Environmental safety and technology-related aspects of mycotoxins; Chemistry, synthesis and analysis.
FI 0.84
Q2
Keywords: Earth; Space & Environmental Sciences; Ecotoxicology & Pollution Science; Acuerdos transformativos; Transformative agreements; Micotoxinas; Hongos toxigénicos; Contaminación alimentaria; Toxicología